2017
DOI: 10.1007/s12291-017-0660-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of CYP2C9 Among Sistani Ethnic Group in Gorgan

Abstract: Cytochrome P450 2C9 (CYP2C9) is involved in metabolism of many important drugs and its genotype variations is thought to affect drug efficacy and the treatment process. The aim of this study was to assess the distribution of CYP2C9 allele and genotypic variants in Sistani ethnic group, living in Gorgan, South East of Caspian Sea and North East of Iran. This study included 140 Sistani, referred to the health center of Gorgan. CYP2C9 genotyping was carried out by polymerase chain reaction-restriction fragment le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In Albanians, Romani and Macedonians, CYP2D6 variants do not differ from other European populations [82]. CYP2C9 allele and genotype variation in the Sistani ethnic group from Gorgan, South East of Caspian Sea and North East of Iran, shows important differences when compared to other populations (CYP2C9*1/*1, 53.9%; CYP2C9*1/*2, 22.1%; CYP2C9*1/*3, 11.4%; CYP2C9*2/*2, 2.9%; CYP2C9*2/*3, 4.3%; CYP2C9*3/*3, 0%) [83].…”
Section: Ethnic Differences In Adrsmentioning
confidence: 93%
“…In Albanians, Romani and Macedonians, CYP2D6 variants do not differ from other European populations [82]. CYP2C9 allele and genotype variation in the Sistani ethnic group from Gorgan, South East of Caspian Sea and North East of Iran, shows important differences when compared to other populations (CYP2C9*1/*1, 53.9%; CYP2C9*1/*2, 22.1%; CYP2C9*1/*3, 11.4%; CYP2C9*2/*2, 2.9%; CYP2C9*2/*3, 4.3%; CYP2C9*3/*3, 0%) [83].…”
Section: Ethnic Differences In Adrsmentioning
confidence: 93%
“…on Caucasians populations, they exposed that the CYP2C9*2 and CYP2C9*3 were more allele frequent comparing to African American and Asian populations while Chinese and Japanese have not showed the CYP2C9*2 allele . The allele frequencies of CYP2C9 differ among different populations and many investigates on CYP2C9 variation in different populations have revealed a significant difference in alleles and genotypes frequency [17,18] . This may be the reason behind the probable ethnic differences to drug response.…”
Section: Cyp2c9 Variants Genotypementioning
confidence: 99%
“…The differences in genotype of enzyme have displayed the association of certain genotypes with a great risk of s-warfarin over bleeding events and anticoagulation in comparing to a wild type . Clinical studies have also suggested that subject with the mutated genotypes require lower doses of S-warfarin (10-20% and/or 20-50%) when compared to a wild type subject [17]…”
Section: Cyp2c9 Variants Genotypementioning
confidence: 99%
“…Hence, acquiring precise information on the (Ataby et al, 2013;Azarpira et al, 2010;Hosseinkhani et al, 2018;Marjani and Gharanjik, 2018;Namazi et al, 2010;Razavi et al, 2017;Tabari et al, 2015;Zand et al, 2007). Ultimately, Fars people possess highest CYP2C9*2 and CYP2C9*3 allele frequencies of 24.34% and 9.8%, respectively.…”
Section: Ppi Pharmacogenomics (With Emphasize On Iran)mentioning
confidence: 99%